Pengaruh Kartu Kuartet Toleransi terhadap Pemahaman Siswa pada Mata Pelajaran PPKN Kelas IV SD - Fatimah, Siti Asfatul; Lian, Bukman; Aryaningrum, Kiki (Jurnal Ilmiah Dikdaya, 2024)
Comprehension ability is the ability to understand information given to students in the form of learning material. One alternative for understanding learning material with interesting learning media is quartet card media. Quartet cards are media in the form of a game including: several number of picture cards which have information about the picture by grouping 4 cards with different subtitles. The aim of the research was to determine the effectiveness of using quartet cards on students' comprehension abilities in class IV PPKN subjects. The research subjects were classes IV.A and IV.D at SDN 235 Palembang. This type of research is Quasi Experimental Design with a Nonequivalent Control Group Design design. The research results were seen after carrying out the pretest, treatment, posttest in the experimental class and control class so that the independent sample t-test calculation results obtained a significant value = 0.00, so the significant value was 0.00 <0.05, meaning that Ho was rejected and Ha was accepted.